On Hydromagnetic Channel Flow of an Oldroyd-B Fluid induced by Pulses of Longitudinal Impulses - Ghosh, Sanchita (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
A flow problem concerning motion of an incompressible electrically conducting Oldroyd-B fluid in a channel bounded by two infinite rigid non-conducting parallel plates in presence of an external magnetic field acting in a direction normal to the plates has been solved in this paper. The unsteady motion is supposed to generate impulsively from rest in the fluid due to pulses of longitudinal impulses applied periodically on the upper plate in its own plane with the lower plate held fixed. There is no external electric field acting on the system and the magnetic Reynolds number is very small. The operational method is used to obtain the exact solutions for the velocity field and the skin-friction on the walls. The influence of the magnetic field and the fluid elasticity on the flow as well as on the skin-frictions are examined quantitatively. Solutons for the hydromagnetic and hydrodynamic situations are derived as special cases of the present analysis.